2016
DOI: 10.2214/ajr.15.15176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Respiratory Position on Contrast Attenuation in Pulmonary CT Angiography: A Prospective Randomized Clinical Trial

Abstract: Pulmonary CTA should be performed in the resting expiratory position, and patients should be instructed to avoid inspiration to achieve the highest possible attenuation in the pulmonary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…Determination of the contrast bolus arrival time is individualized applying either the test-bolus method or bolus tracking. The best patient's breathing maneuver during data acquisition of pCTA, however, is still a matter of debate [2][3][4][5]. Deep inspiration might lead to increased influx of non-contrast-enhanced blood from the inferior vena cava (IVC) to the right atrium, thus diluting or even interrupting the contrast material influx [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the contrast bolus arrival time is individualized applying either the test-bolus method or bolus tracking. The best patient's breathing maneuver during data acquisition of pCTA, however, is still a matter of debate [2][3][4][5]. Deep inspiration might lead to increased influx of non-contrast-enhanced blood from the inferior vena cava (IVC) to the right atrium, thus diluting or even interrupting the contrast material influx [4].…”
Section: Introductionmentioning
confidence: 99%
“…A small prospectively randomized clinical trial, including 28 patients with suspected PE, suggested pCTA should be performed in resting expiratory state [5]. Attenuation of the blood pool in the cardiac chambers, pulmonary artery and ascending aorta was measured and compared in a larger, but retrospective study including 145 pCTA-examinations in inspiratory and 181 in expiration [2].…”
Section: Introductionmentioning
confidence: 99%
“…One possible cause is the use of breath-hold in end-inspiration. A recent study has shown that pulmonary CTA should be performed in the resting expiratory position [25]. The image quality of pulmonary artery depiction in CTA can be further improved by using a weight-adapted contrast bolus [26].…”
Section: Discussionmentioning
confidence: 99%
“…When flow artefact is suspected, a repeat expiratory CTPA with more delayed and prolonged contrast injection is recommended. [6][7][8]…”
Section: Customer Servicementioning
confidence: 99%